2002
DOI: 10.1890/0012-9658(2002)083[0104:befcco]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Belowground Ectomycorrhizal Fungal Community Change Over a Nitrogen Deposition Gradient in Alaska

Abstract: Nitrogen availability may be a major factor structuring ectomycorrhizal fungal communities. Atmospheric nitrogen (N) deposition has been implicated in the decline of ectomycorrhizal fungal (EMF) sporocarp diversity. We previously characterized the pattern of decreased sporocarp species richness over an anthropogenic N deposition gradient in Alaska (USA). To determine whether this change in sporocarp community structure was paralleled below ground, we used molecular and morphological techniques to characterize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
345
4
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 526 publications
(386 citation statements)
references
References 50 publications
29
345
4
4
Order By: Relevance
“…The vast majority of information about fungal responses to N deposition focuses on mycorrhizal (especially ectomycorrhizal) fungi (Treseder, 2004). In general, studies show that ectomycorrhizal diversity declines with N deposition (Lilleskov et al, 2001(Lilleskov et al, , 2002Frey et al, 2004), and our data indicate that this pattern may be generalizable to broader groups of fungi. Although diversity studies on non-mycorrhizal taxa are rare, there is evidence that wood-decaying fungi compete poorly under high-N conditions (Fog, 1988).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The vast majority of information about fungal responses to N deposition focuses on mycorrhizal (especially ectomycorrhizal) fungi (Treseder, 2004). In general, studies show that ectomycorrhizal diversity declines with N deposition (Lilleskov et al, 2001(Lilleskov et al, , 2002Frey et al, 2004), and our data indicate that this pattern may be generalizable to broader groups of fungi. Although diversity studies on non-mycorrhizal taxa are rare, there is evidence that wood-decaying fungi compete poorly under high-N conditions (Fog, 1988).…”
Section: Discussionsupporting
confidence: 54%
“…Therefore, predicting N deposition and/or climate warming effects on ecosystem processes depends on understanding fungal responses to increasing N availability. There is evidence that N deposition decreases the diversity of ectomycorrhizal fungi in white spruce forests of Alaska (Lilleskov et al, 2001(Lilleskov et al, , 2002, and a recent meta-analysis indicated that N fertilization reduces mycorrhizal abundance by 15% (Treseder, 2004). However, mycorrhizal fungi are not believed to play a major role in organic carbon decomposition (Read, 1991;Dighton, 2003), and the responses of decomposer fungi to N deposition remain largely untested.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in a highly acidic spruce forest soil, the amounts of dissolved organic C (DOC) and dissolved N were found to be very low (Bárta et al 2010). It is well accepted that mycorrhizal fungi exert strong controls over belowground C allocation in forest ecosystems, greatly affecting microbial turnover in the rhizosphere (Janssens et al 2010;Kuzyakov and Xu 2013;Lilleskov et al 2001Lilleskov et al , 2002Tietema 1998;Treseder 2008). Here, we further conjecture that the change in mycorrhizal fungi, resulting from Al 3 + release in the process of soil acidification, is likely to play a role in the decreased N mineralization.…”
Section: N Mineralizationmentioning
confidence: 99%
“…Furthermore, increased nitrogen loadings can affect ecosystem phosphorus cycling, as observed in a wide variety of terrestrial ecosystems 54 , by favouring higher plant phosphorus uptake e.g. through enhanced activity of soil phosphatases 55 , root phosphatases 56 or changing symbiotic fungi 57 . Nonetheless, in the long term, these mechanisms seem quantitatively insufficient to deliver enough phosphorus to alleviate phosphorus limitation 58 .…”
Section: Discussionmentioning
confidence: 99%